Digitization process of library resources in higher education institutions in La Union - Lacuata, Ana Nova P. (Saint Louis College, City of San Fernando, La Union : [s.n.], 2018)
This descriptive research determined the extent of implementation of the guidelines in digitization of resources in the libraries oh HEIs in La Union along selection, technical requirement and implementation, legal aspects, budget, human resource planning, development and maintenance, preservation of digital content and project management; and the strengths and weaknesses on digitization of resources. Data gathered using the validated and pretested questionnaire was treated using percentage, ranking and weighted mean.
Bibliography: pages 85-94.
CHED-La Union
Keywords: Library resources -- Conservation and restoration